Melatonin Alleviates Photosynthetic Injury in Tomato Seedlings Subjected to Salt Stress via OJIP Chlorophyll Fluorescence Kinetics - Xianjun Chen; Xiaofeng Liu; Yundan Cong; Yao Jiang; Jianwei Zhang; Qin Yang; Huiying Liu (Plants)
The tomato is among the crops with the most extensive cultivated area and greatest consumption in our nation; nonetheless, secondary salinization of facility soil significantly hinders the sustainable growth of facility agriculture. Melatonin (MT), as an innovative plant growth regulator, is essential in stress responses. This research used a hydroponic setup to replicate saline stress conditions. Different endogenous levels of melatonin (MT) were established by foliar spraying of 100 μmol·L−1 MT, the MT synthesis inhibitor p-CPA (100 μmol·L−1), and a combination of p-CPA and MT, to investigate the mechanism by which MT mitigates the effects of salt stress on the photosynthetic efficiency of tomato seedlings. Results indicated that after six days of salt stress, the endogenous MT content in tomato seedlings drastically decreased, with declines in the net photosynthetic rate and photosystem performance indices (PItotal and PIabs). The OJIP fluorescence curve exhibited distortion, characterized by anomalous K-band and L-band manifestations. Exogenous MT dramatically enhanced the gene (TrpDC, T5H, SNAcT, and AcSNMT) expression of critical enzymes in MT synthesis, therefore boosting the level of endogenous MT. The application of MT enhanced the photosynthetic parameters. MT treatment decreased the fluorescence intensities of the J-phase and I-phase in the OJIP curve under salt stress, attenuated the irregularities in the K-band and L-band performance, and concurrently enhanced quantum yield and energy partitioning ratios. It specifically elevated φPo, φEo, and ψo, while decreasing φDo. The therapy enhanced parameters of both the membrane model (ABS/RC, DIo/RC, ETo/RC, and TRo/RC) and leaf model (ABS/CSm, TRo/CSm, ETo/CSm, and DIo/CSm). Conversely, the injection of exogenous p-CPA exacerbated salt stress-related damage to the photosystem of tomato seedlings and diminished the beneficial effects of MT. The findings suggest that exogenous MT mitigates salt stress-induced photoinhibition by (1) modulating endogenous MT concentrations, (2) augmenting PSII reaction center functionality, (3) safeguarding the oxygen-evolving complex (OEC), (4) reinstating PSI redox potential, (5) facilitating photosynthetic electron transport, and (6) optimizing energy absorption and dissipation. As a result, MT markedly enhanced photochemical performance and facilitated development and salt stress resilience in tomato seedlings.